An Improved Method for Selection of Seed Stands for Conversion into Seed Production Areas - Mandal, A. K.; Lal, R. B.; Gupta, B. N. (Indian Forester, 1998)
No suitable methods were available for selection of seed stands of unknown origin for conversion into seed production areas. The method described in this paper will be suitable for stands of unknown origin.